2015
DOI: 10.1111/asj.12385
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐chemical characteristics of Longissimus lumborum muscle in goats subjected to halal slaughter and anesthesia (halothane) pre‐slaughter

Abstract: This study assessed the effect of halal slaughter and anesthesia pre-slaughter followed by bleeding on meat quality characteristics of goats. Eleven male Boer cross goats were divided into two groups and subjected to either halal slaughter (HS) or anesthesia with halothane and propofol pre-slaughter (AS). At pre-rigor, HS had significantly lower (P < 0.05) muscle pH and glycogen than AS. However, no significant difference was observed in the pH and glycogen content between the treatments on 1, 3 and 7 days pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 68 publications
(130 reference statements)
11
28
0
Order By: Relevance
“…This could be attributed to the postmortem muscle structural breakdown caused by the disruption of the channels through which water is lost, resulting in the formation of a 'sponge effect' that traps the water and prevents it from getting lost (Farouk et al, 2014). The present observation corroborates the findings of Sabow et al (2015b) who observed a decrease in the cooking loss of chevon as postmortem storage progressed.…”
Section: Drip and Cooking Lossessupporting
confidence: 87%
See 4 more Smart Citations
“…This could be attributed to the postmortem muscle structural breakdown caused by the disruption of the channels through which water is lost, resulting in the formation of a 'sponge effect' that traps the water and prevents it from getting lost (Farouk et al, 2014). The present observation corroborates the findings of Sabow et al (2015b) who observed a decrease in the cooking loss of chevon as postmortem storage progressed.…”
Section: Drip and Cooking Lossessupporting
confidence: 87%
“…Regardless of slaughter method, drip loss increased (P < 0.05) as postmortem storage continued. This observation could be due to the degradation of myofibrillar proteins by endogenous proteases, thus affecting the ability of muscle to hold water Sabow et al, 2015b). Similar finding was observed during postmortem conditioning of broiler chickens Savenije et al, 2002).…”
Section: Drip and Cooking Lossessupporting
confidence: 77%
See 3 more Smart Citations